2019
DOI: 10.1038/s41598-019-51042-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Spatial Agglomeration of Agricultural Drought Disaster in China from 1978 to 2016

Abstract: Drought disaster space agglomeration assessment is one of the important components of meteorological disaster prevention and mitigation. Agriculture affected by drought disaster is not only a serious threat to world food security, but also an obstacle to sustainable development. Additionally, China is an important agricultural import and export country in the world. Therefore, we used the global Moran’s I and the local indicators of spatial autocorrelation (LISA) to reveal the spatial agglomeration of agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…RSI is the rainfall intensity comprehensive index. Its calculation method is shown in formula (1). V H is the sensitivity index, and the calculation method is shown in formula (2).…”
Section: Heavy Rain Disaster Risk Assessment Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…RSI is the rainfall intensity comprehensive index. Its calculation method is shown in formula (1). V H is the sensitivity index, and the calculation method is shown in formula (2).…”
Section: Heavy Rain Disaster Risk Assessment Modelmentioning
confidence: 99%
“…Foreign scholars have done a lot of research on the methods of storm disaster risk assessment. They believe that the formation of disasters results from the comprehensive effects of the carrier's vulnerability, hazards and exposure [1]. The risk assessment method proposed by scholars has certain practicability.…”
Section: Introductionmentioning
confidence: 99%
“…Abebe Senamaw et al ( 2021 ) used the Vegetation Condition Index eMODIS NDVI and SPI between 2000–2016 to show the spatial and temporal variations of agricultural drought and meteorology in Ethiopia. Qian Wang et al ( 2019 ) assessed the spatial aggregation of the agricultural drought crisis in China between 1978–2016 using the Global Moran's Index (GMI) and the Local Indicators of Spatial Association. They reported that the direction of the drought crisis was toward the northwest.…”
Section: Introductionmentioning
confidence: 99%
“…China is a major agricultural‐producing country but is highly drought‐prone (Wang et al., 2019; Zhang et al., 2018). As per relevant statistical data from the period of 1978–2016, the average annual agricultural loss area due to droughts is approximately 2.27 million hectares, accounting for more than half of the total agricultural loss area (Wang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%